What Is Christianity? : An Introduction to the Christian Religion - Ramshaw, Gail, 1947- (Book collections on Project MUSE., 2013)
Gail Ramshaw frames this new introduction to Christianity around the basic questions that students ask. Investigating Christianity as a lived experience, she opens each chapter with a voice from the field of religious studies and then presents answers to each chapter's question by surveying the history, doctrine, practices, and convictions of Christian churches. Written for undergraduates with little or no background in the breadth of Christianity, the text of the book reports on the diversity of Christian belief and practice, and is accompanied with student-friendly learning helps, including side-bar definitions, art, photos, study questions, essay topics, and suggestions for further exploration in short stories, novels and films.